PHYSICOCHEMICAL PROPERTIES OF OILS EXTRACTED FROM Azadirachta indica SEEDS - OWOICHO OKPANACHI, GIDEON; GAZA ZARUMAI, UMAR FAROUK; MOHAMMED, JIBRIN; RASAQ ODUOLA, ADEMOLA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The applications of Azadirachta indica seed oil are defined by its property through many factors, including methods by which the oil was extracted. The study compared the physicochemical properties of the oils extracted from Azadirachta indica seeds with standard values. The Azadirachta indica seeds were collected from Gombe State Nigeria and the neem seed oils (NSO) were extracted through the Soxhlet method using n- hexane and by mechanical extraction using water as a solvent to get NSO A and NSO B respectively. The percentage yields of both oils were determined and thereafter, their physicochemical properties were carried out. The physical properties of the oils and their physicochemical characteristics had comparable values with the standard. The overall study proved that the extraction methods had impact on the quality of the oil. The medicinal values of NSO could be exploited and put into clinical uses in the production of antiseptic soaps, lubricants, creams, shampoo, insect repellants, etc.